Shaping the Future : Long-Term Perspectives on People and Job Mobility for MENA - Zlaoui, Leila (World Bank, Washington, DC, 2012)
This quick note summarizes the similarly titled report released on February 17, 2009, which assesses global labor and job mobility that is migration and outsourcing with a focus on Europe and Middle East and North Africa (MENA). The report looks at long term global demographic and labor force developments to assess which parts of the world will experience aging populations and major declines in their labor force and which will see an expansion. Two pillars underpin the analysis presented in this report. First, increasingly strong forces will be pulling for the migration of people and jobs across the world's regions in the future. Second, countries and regions can adopt a proactive approach to prepare for these global changes, to seize opportunities, and to address risks head on.